Exploring gut microbiota alterations in Parkinson’s disease: insights from a 16S amplicon sequencing Eastern European pilot study - Ilie, Ovidiu-Dumitru; Văcărean-Trandafir, Irina-Cezara; Amărandi, Roxana-Maria; Nita, Ilinca-Bianca; Dobrin, Petru-Romeo; Doroftei, Mara; Ivanov, Iuliu-Cristian; Savuta, Gheorghe; Kirov, Boris; Doroftei, Bogdan (Frontiers in Neuroscience, 2025)
IntroductionParkinson’s disease (PD) is a neurodegenerative disorder increasingly associated with alterations in gut microbiota through the gut–brain axis (GBA). Despite growing global interest, studies examining microbiota composition in Eastern European populations remain limited.MethodsWe profiled the gut microbiota of 59 Romanian individuals using 16S rRNA gene sequencing targeting the V3–V4 region. After quality filtering, 39 subjects (19 PD patients and 20 healthy controls [HC]) were retained for downstream analysis. Clinical metadata were collected to assess potential confounders, including age, sex, metabolic parameters, lifestyle, and comorbidities.ResultsPD patients differed significantly from HCs in glycemia (p = 0.02), cholesterol (p = 0.027), and LDL levels (p = 0.047), and more frequently presented with restrictive diets and comorbidities such as cardiovascular disease and diabetes. While α-diversity metrics did not differ significantly between groups, principal coordinate analysis (PCoA) based on Aitchison distance showed moderate compositional separation. Permutational multivariate analysis of variance (PERMANOVA) confirmed that disease status was a significant driver of gut microbiota composition (R2 = 5.3%, p = 0.002), independent of clinical and lifestyle covariates. Sparse partial least square linear discriminant (sPLS-DA) identified several genera distinguishing PD from HC, with Mogibacterium and RikenellaceaeRC9 gut group enriched in PD, and several known short-chain fatty acid (SCFA)-producing genera (Fusicatenibacter, Lachnospiraceae UCG-001, Butyricicoccus, Anaerostipes) enriched in HCs. Linear discriminant analysis (LDA) Effect Size (LEfSe) corroborated these findings, confirming the differential abundance of several SCFA-producing genera in the HC group.DiscussionOur results reveal distinct microbial signatures associated with PD in this Romanian cohort, marked by a consistent depletion of SCFA-producing bacteria in patients. These findings support the role of gut microbiota in PD pathophysiology and underscore the need for further studies in Eastern European populations.